2017
DOI: 10.1002/asia.201701323
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared‐Emissive Amphiphilic BODIPY Assemblies Manipulated by Charge‐Transfer Interaction: From Nanofibers to Nanorods and Nanodisks

Abstract: A novel near-infrared (NIR)-emissive amphiphilic BODIPY derivative, BBDP, was successfully prepared and thoroughly characterized. The photophysical properties in various organic solvents and THF/H O mixtures with different fractions of water were investigated. BBDP self-assembled into nanofibers in a water environment owing to its amphiphilic properties. Through charge-transfer interactions, BBDP co-assembled with a perylene bisimide derivative, PBI, and a viologen derivative, MV, to generate two superamphiphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 63 publications
(131 reference statements)
0
9
0
1
Order By: Relevance
“…To improve the potential affinity of the functional dyes toward the nanocarbon materials, we designed several new BODIPY-centered pyrene conjugates (Scheme ) in which one or two pyrene fragments are fully conjugated into the BODIPY’s π-system. Although a few pyrene–BODIPY conjugates similar to those reported here were previously reported, their interaction with nanocarbon materials, as well as electron-transfer properties in noncovalent assemblies with nanocarbon arrays, was not targeted. To the best of our knowledge, this report is the first investigation of the noncovalent assemblies formed between fully conjugated pyrene–BODIPY chromophores and nanocarbon acceptors.…”
Section: Introductionmentioning
confidence: 89%
“…To improve the potential affinity of the functional dyes toward the nanocarbon materials, we designed several new BODIPY-centered pyrene conjugates (Scheme ) in which one or two pyrene fragments are fully conjugated into the BODIPY’s π-system. Although a few pyrene–BODIPY conjugates similar to those reported here were previously reported, their interaction with nanocarbon materials, as well as electron-transfer properties in noncovalent assemblies with nanocarbon arrays, was not targeted. To the best of our knowledge, this report is the first investigation of the noncovalent assemblies formed between fully conjugated pyrene–BODIPY chromophores and nanocarbon acceptors.…”
Section: Introductionmentioning
confidence: 89%
“…Knowledge of the size–property relationship helps in designing new materials with tailor‐made properties. Aggregation of molecules within nanomaterials often leads to significant changes in electronic properties compared with those in solution . This characteristic has allowed fine‐tuning of the photophysical properties of nanomaterials and has led to a variety of applications in materials science, molecular recognition, live cell imaging, and theranostics …”
Section: Figurementioning
confidence: 99%
“…found that the micelle aggregate of amphiphilic block copolymer using BODIPY as linkage would decompose upon visible light irradiation . In our previous work, we also reported that the hydrophobic and hydrophilic structural moieties work in concert to regulate the BODIPY‐based supramolecular polymers morphology and photophysical properties . In this work, we synthesized a novel kind of photoresponsive main chain SDP by taking advantage of host–guest interaction between γ‐CD and BODIPY derivative BDPC.…”
Section: Methodsmentioning
confidence: 97%